Gender Inequity in the Corporate Sector in India - Gawali, Vidya Sandu (Prabandhan: Indian Journal of Management, 2012)
The conditions of women at the workplace are based on conservative outlook of the employers that positions them at the periphery of the workplace that had no meaningful contribution to the growth and development. Many reports and surveys show that women's situation at workplaces are not satisfactory. Thus, the present paper highlights the gender discrimination in the corporate sector in India in terms of work and pay. According to the Census 2011, the female population is 48.46 % in India , but opportunities they are getting are not even 40%. This paper gives a brief about the participation of women in the corporate sector of India, and their status in senior managerial positions in India. The paper also highlights the gender wage gap in India as compared to other countries. The suggestion given in this paper will be definitely helpful for improving the status of women in India.